2019
DOI: 10.1111/pde.13943
|View full text |Cite
|
Sign up to set email alerts
|

Wait times, health care touchpoints, and nonattendance in an academic pediatric dermatology clinic

Abstract: Background and objectives Timely access to pediatric dermatology care remains a challenge. While awaiting appointments, many patients and families utilize so‐called health care touchpoints outside of the dermatology clinic such as primary care or emergency department visits to address dermatologic concerns. Long waiting periods also factor into nonattendance rates at pediatric dermatology appointments. This observational retrospective study investigated wait times, relevant health care touchpoints, and factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 13 publications
1
26
1
1
Order By: Relevance
“…Attendance rates in paediatric outpatient services are traditionally poor and high non‐attendance rates are an additional cost to the service. Although the non‐attendance rates in this study appear to be substantial, they are in line with reported attendance rates for paediatric services generally 14,15 . Comparing the two groups, the likelihood of attendance was 2.6 times higher for the AA group for their first appointment compared to the ENT group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Attendance rates in paediatric outpatient services are traditionally poor and high non‐attendance rates are an additional cost to the service. Although the non‐attendance rates in this study appear to be substantial, they are in line with reported attendance rates for paediatric services generally 14,15 . Comparing the two groups, the likelihood of attendance was 2.6 times higher for the AA group for their first appointment compared to the ENT group.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing the two groups, the likelihood of attendance was 2.6 times higher for the AA group for their first appointment compared to the ENT group. Longer waiting times have been shown to be significantly associated with reduced attendance rates in paediatric dermatological outpatient services, 15 as well as non‐attendance rates increasing during the winter to spring months suggesting a seasonal element. In the case of middle ear disease, it is possible that children who have been waiting longer no longer require the service to which they have been referred due to the transient nature of a substantial proportion of middle ear disease.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age has been associated with increased visits to primary care and the emergency department in response to long wait times for pediatric dermatology appointments 15 . Patients who received a recommendation for FTF evaluation were younger on average than those who did not, and the eConsult program helped hasten their access to dermatology recommendations (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the control study, patients referred to a pediatric dermatologist waited on average 80 days for an in-person appointment, with longer wait times associated with increased rates of interim health care touchpoints, appointment cancelation, and failure to attend (noshow) a scheduled outpatient visit. 9 found that once established with a provider, patients may be reluctant to switch from one provider to another. 10,11 While teledermatology has the potential to expand access for patients in need, downstream consequences should be considered, such as creation of additional work for PCP and consulting specialists.…”
Section: Areas For Improvementmentioning
confidence: 99%